2014
DOI: 10.1007/s00264-014-2334-x
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical comparison of fixed angle locking compression plate osteosynthesis and cement augmented screw osteosynthesis in the management of intra articular calcaneal fractures

Abstract: Purpose The purpose of this study was to investigate whether cement-augmented screw osteosynthesis results in stability comparable to conventional fixed-angle locking plate osteosynthesis using cadaveric bones to model a Sanders type 2B fracture. Methods Seven pairs of fresh frozen human calcanei and the corresponding tali were used. The specimens were assigned pairwise to two study groups in a randomised manner. In order to determine the initial quasi-static stiffness of the boneimplant construct, testing com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The loading protocol was adopted from previous studies performed by Rausch et al [ 12 ] and Marks et al [ 4 ]. It comprised initial quasi-static ramped compression loading from 20 N to 150 N at a rate of 13N/s, followed by cyclic axial compression at a rate of 2 Hz with progressively increasing loading and physiological profile of each cycle.…”
Section: Methodsmentioning
confidence: 99%
“…The loading protocol was adopted from previous studies performed by Rausch et al [ 12 ] and Marks et al [ 4 ]. It comprised initial quasi-static ramped compression loading from 20 N to 150 N at a rate of 13N/s, followed by cyclic axial compression at a rate of 2 Hz with progressively increasing loading and physiological profile of each cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Previous findings in biomechanical studies regarding bone substitutes in calcaneal fracture treatment were promising. No matter if bone substitutes were applied by injection through cannulated screws or as solid block, the stability always increased [ 11 , 13 , 18 , 19 ]. The calcanei treated with bone cement showed significantly less deformation in cyclic testing, and the authors reported a large increase in strength of the construct that possibly leads to more rapid rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…(17), it was emphasized that percutaneous screw fixation of calcaneus fractures may provide a strength similar to that of plate fixation. Different implants can be used for fracture synthesis and the goal is to achieve enough stability to promote early active range of motion, without weight bearing and redisplacement of the fragments (18,19).…”
Section: Discussionmentioning
confidence: 99%